Gold Installment Marketing Strategy to Increase Customer Interest at BSI Situbondo Branch - Uthulul Jannah; Citra Dwi Puspita; Elvin Adria Saputri; Suprianik (CV Edujavare Publishing, 2026)
Bank Syariah Indonesia (BSI) provides financing services for gold purchases known as BSI Gold Installments (CILEM). This product is a funding service that allows customers to own gold through an installment payment system. This product scheme uses a murobahah contract as the basis of the agreement, and is supported by a rahn (pawn) contract as collateral. The gold used is in the form of gold bars, bullion, or Antam precious metals with an initial payment of 20% while the remaining 80% can be paid in stages. This study aims to determine how the Cilem marketing strategy increases public interest in becoming customers at BSI KCP Situbondo. The method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation conducted at BSI KCP Situbondo. The results show that the offering strategy through WhatsApp blast is the most effective way to attract new customers. The combination of the two strategies is sustainable for long-term investment.